Science and the production of knowledge in educational research: contributions of Maria Célia Marcondes de Moraes - Patricia Laura Torriglia; Newton Duarte (Universidade Federal de Santa Catarina, 2010)
This article presents important issues related to the problem of science and production of knowledge in education raised in different works written by Maria Célia Marcondes de Moraes. Various theoretical problems concern the author, in particular the current skepticism and the profound contradictions in which meanings and concepts that signify theoretical practical movements present themselves with subtle and marked inversions and the impacts of this skepticism on the field and in educational research. Based on a materialist and critical ontological perspective, Moraes questions, discusses and delves into issues concerning the social being in its maximum expression.